Relative age effects in German youth A and B men's soccer teams: survival of the fittest? - Heilmann, F.; Kuhlig, A.; Stoll, O. (Frontiers in Sports and Active Living, 2024)
The study investigates relative age effects (RAE) in German youth soccer (Youth Bundesliga A: January 2004 to December 2005 and B: January 2006 to December 2007; highest league in German youth soccer) and its persistence in third-division players. Data from the 2022-2023 season (120 teams, 3,174 players) were analyzed using chi-square tests. Significant RAE was found in the A-series (p < .001), B-series (p < .001), and third-division professionals (p < .001). Notably, RAE was prominent among younger players but less evident in older third-division players (p = .116), indicating a diminishing selection effect with age and professional tenure. Coaches and talent managers are advised to consider RAE and additional factors like player maturity in talent selection for more efficient talent management strategies, especially in youth academies.